Enhanced legume root growth with pre-soaking in α-Fe2O3 nanoparticle fertilizer. Issue 43 (2nd July 2018) - Palchoudhury, Soubantika; Jungjohann, Katherine L.; Weerasena, Lakmali; Arabshahi, Abdollah; Gharge, Uday; Albattah, Abdulaziz; Miller, Justin; Patel, Ketan; Holler, Robert A.
Abstract : A new approach to increase root growth in legumes by pre-soaking seeds in iron oxide nanoparticle growth solution. Abstract : The rising demand for food and energy crops has triggered interest in the use of nanoparticles for agronomy. Specifically, iron oxide-based engineered nanoparticles are promising candidates for next-generation iron-deficiency fertilizers. We used iron oxide and hybrid Pt-decorated iron oxide nanoparticles, at low and high concentrations, and at varied pHs, to model seed pre-soaking solutions for investigation of their effect on embryonic root growth in legumes. This is an environmentally friendly approach, as it uses less fertilizer, therefore less nanoparticles in contact with the soil. Analysis from varied material characterization techniques combined with a statistical analysis method found that iron oxide nanoparticles could enhance root growth by 88–366% at low concentrations (5.54 × 10 −3 mg L −1 Fe). Hybrid Pt-decorated iron oxide nanoparticles and a higher concentration of iron oxide nanoparticles (27.7 mg L −1 Fe) showed reduced root growth. The combined materials characterization and statistical analysis used here can be applied to address many environmental factors to finely tune the development of vital nanofertilizers for high efficiency food production.